52.4k views
18 votes
Please help, explain in words the steps needed to solve this problem

Please help, explain in words the steps needed to solve this problem-example-1
User Yantrab
by
4.5k points

1 Answer

7 votes

Answer:

x=6

Step-by-step explanation:

By the Product Rule of Logarithms, the logarithm of the product of numbers is the sum of the logarithms of the numbers.


log(x) + log(x - 1) = log(x(x - 1)) = log( {x}^(2) - x ) = log(3x + 12)

Raise both sides to the power of 10 to eliminate the logs, obtaining:


{x}^(2) - x = 3x + 12


{x}^(2) - 4x - 12 = 0


(x - 6)(x + 2) = 0

x = -2 or x = 6. Since x = -2 is extraneous, it follows that x = 6.

User Woutvdd
by
4.5k points